Clinical features associated to refractory obsessive-compulsive disorder - Ferrao, Ygor A.; Shavitt, Rosell G.; Bedin, Nadia R.; de Mathis, Maria Eugenia; Lopes, Antonio Carlos; Fontenelle, Leonardo F.; Torres, Albina Rodrigues [UNESP]; Miguel, Euripedes C. (Elsevier B.V., 2006)
Some patients with obsessive-compulsive disorder (OCD) exhibit an unsatisfactory reduction in symptom severity despite being treated with all the available therapeutic alternatives. The clinical variables associated with treatment-refractoriness in OCD are inconsistently described in the literature.Methods: To investigate factors associated with treatment-reftactoriness of patients with OCD, we conducted a case-control study, comparing 23 patients with treatment-refractory OCD to 26 patients with treatment-responding OCD.Results: the factors associated with refractoriness of OCD were higher severity of symptoms since the onset of OCD (P < 0.001), chronic course (p=0.003), lack of a partner (p=0.037), unemployment (p=0.025), low economic status (p=0.015), presence of obsessive-compulsive symptoms of sexual/religious content (p=0.043), and higher scores on family accommodation (P < 0.001). Only the three latter variables remained significantly associated with treatment-reftactoriness after regression analyses. Limitations: small sample size, the biases and drawbacks inherent to a case-control study, and the inclusion criteria used to define the study groups may have limited the generalisation of the results.Conclusion: A major strength of this study is the systematic and structured evaluation of a vast array of variables related to the clinical expression of OCD, including epigenetic factors and ratings derived from instruments evaluating family accommodation. The presence of sexual/religious symptoms, low economic status and high modification on family function due to OCD were independently associated with, treatment-refractoriness. Future longitudinal studies are warranted to verify if these variables represent predictive factors of treatment non-response. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: obsessive-compulsive disorder; treatment response; predictive factors